Alkaline hydrolyzed torula yeast as an attractant for Anastrepha obliqua (Diptera: Tephritidae). (7th April 2022) - Lasa, Rodrigo; Williams, Trevor
Abstract: Acid hydrolyzed proteins with borax and torula yeast pellets are attractants commonly used for monitoring the West Indian fruit fly, Anastrepha obliqua (Macquart). Alkaline hydrolysis of proteins has been poorly studied as a source of attractants for tephritids, despite it increasing the production of ammonia, a known attractant for A . obliqua and other tephritids. Laboratory experiments revealed a significantly greater response of flies to torula yeast alkalized with NaOH at pH 10.3, 11.3, 12.3 and 13.3 compared with torula yeast + borax at pH 9.15. Traps baited with alkalized torula yeast at pH 13.3 captured significantly higher numbers of flies than torula yeast at pH 10.3, 11.3 or 12.3. The emission of ammonia from these traps was positively correlated with pH. Anastrepha obliqua was less attracted to torula yeast at pH 13.3 when alkalized with KOH than with NaOH, although no significant differences were detected in the emission of ammonia. In mango orchards in Mexico, the mean number of A . obliqua flies per trap per day was higher for traps baited with torula yeast at pH 13.3 than for acid hydrolyzed protein + borax or torula yeast pellets containing borax. While ammonia emissions from torula yeast at pH 13.3 and acid hydrolyzed protein + borax were reduced after one week in the field, the ammonia emission of torula yeast pellets increased after one week to levels similar to those of the other attractants. Alkaline hydrolysis of torula yeast at pH 13.3 increased the release of ammonia, reduced the surface tension of the liquid and proved more effective at capturing A . obliqua flies in laboratory cages and mango orchards when compared with standard attractants. This preparation is simple, cheap and stable and could find application in monitoring programmes targeted at A . obliqua .